If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5(4 + -1x) + 3 = 14 + -1(-5 + 2x) 2x + (4 * -5 + -1x * -5) + 3 = 14 + -1(-5 + 2x) 2x + (-20 + 5x) + 3 = 14 + -1(-5 + 2x) Reorder the terms: -20 + 3 + 2x + 5x = 14 + -1(-5 + 2x) Combine like terms: -20 + 3 = -17 -17 + 2x + 5x = 14 + -1(-5 + 2x) Combine like terms: 2x + 5x = 7x -17 + 7x = 14 + -1(-5 + 2x) -17 + 7x = 14 + (-5 * -1 + 2x * -1) -17 + 7x = 14 + (5 + -2x) Combine like terms: 14 + 5 = 19 -17 + 7x = 19 + -2x Solving -17 + 7x = 19 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -17 + 7x + 2x = 19 + -2x + 2x Combine like terms: 7x + 2x = 9x -17 + 9x = 19 + -2x + 2x Combine like terms: -2x + 2x = 0 -17 + 9x = 19 + 0 -17 + 9x = 19 Add '17' to each side of the equation. -17 + 17 + 9x = 19 + 17 Combine like terms: -17 + 17 = 0 0 + 9x = 19 + 17 9x = 19 + 17 Combine like terms: 19 + 17 = 36 9x = 36 Divide each side by '9'. x = 4 Simplifying x = 4
| (2x^2+5x)(20x^2-7x-3)=0 | | 2y(y-1)=3-y | | 5(x+5)(x-10)=2(2.5x*x-1.9) | | 48=-8w | | 5(x+5)(x-10)=8.7 | | 9=2x-4 | | 5(x+5)(x-10)=12.5x-3.8 | | x-1.4=5.7 | | (x-7)(x+2)=x*x+10 | | x+2x-15=12 | | 5(-3-2x)=4 | | 4*8(x-4)=2x | | 2*8(x-4)=2x | | y=-0.02x^2+x+2 | | 2.1x-5.7=3.9(4.3-1.8x) | | 4x+2=3(x-1)+2 | | 4x-x=x+8 | | 4x+2=8x-14 | | 48-(18-58x)=28-(17+18x-57) | | 25x=22 | | 2x+1=5+x | | 0.5x-8=-3(0.5x+2) | | 12x-22=9x-29 | | x-2(x^2-4x+4)+x-2=0 | | x^2-4x+1=o | | 2(x+1)+7=2x+9 | | 7x+2=3x+1 | | 3(4)(7)= | | 2x+3-4x=7(x-5) | | 4.7(2f-0.5)=-61(1.6f-8.3f) | | 3x+6(2-x)-13= | | (x-2)(x-3)=(x+2)(x+3) |